Primary + Early Childhood = chalk and cheese? Tensions in undertaking an early childhood/primary education degree. Issue 1 (March 2019) - Boyd, Wendy; Newman, Linda
There is well-established evidence that the quality of early childhood education workforce impacts upon children's learning. Attracting qualified teacher graduates to work in early childhood centres is an essential component towards the provision of quality care. Significant investment by the Australian Government has been made to prepare early childhood teachers, yet teaching at this level is characterised by poorer working conditions compared with primary school teachers. Various programme models qualify applicants as early childhood teachers, yet there is no evidence of the most appropriate model. Our study's focus was to identify reasons for entering a teacher education programme, career intentions and satisfaction of pre-service teachers enrolled in early childhood/primary degree programmes at two Australian universities. Findings demonstrate that the degrees were not fulfilling the government investment goals for increasing early childhood teacher numbers, nor were the degrees meeting student expectation for an early childhood teaching career. We argue that renewed policy strategies are required to support new early childhood graduates and professionals, and attract teachers to work in early childhood education.